2013
DOI: 10.1063/1.4775408
|View full text |Cite
|
Sign up to set email alerts
|

An experimental acoustic cloak for generating virtual images

Abstract: A two-dimensional acoustic cloak is realized to generate virtual image in air. The cloak is designed to make the backscattering characteristics of a quadrangular prism the same as that of a plate based on transformation acoustics. The required anisotropic parameters of the cloak shell are obtained by acoustic metamaterial made of perforated plates, which are easy to fabricate and unitize. The measurements of the backward and near-backward scattering fields confirm the validity of the proposed cloak. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The good cloak effect was shown by the experimental results. Since then, more relative researches on carpet cloak for airbone sound have been reported [17][18][19]. Compared with carpet cloak for airbone sound, the underwater one has more important practical applications, but suffering from difficulty in impedance matching and microstructure design [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The good cloak effect was shown by the experimental results. Since then, more relative researches on carpet cloak for airbone sound have been reported [17][18][19]. Compared with carpet cloak for airbone sound, the underwater one has more important practical applications, but suffering from difficulty in impedance matching and microstructure design [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Zhang, et al 5 made a 2D cylindrical acoustic cloak for underwater ultrasound based on transmission line approach. Hu, et al 6 fabricated the 2D rhombic acoustic cloak with perforated plates. Zigoneanu, et al 7 realized the three-dimensional broadband omnidirectional acoustic ground cloak based on their 2D model in air 8 .…”
mentioning
confidence: 99%
“…Since the properties of the four sections are the same, we can just calculate the section in the first quadrant. The interior and exterior boundaries in the first quadrant can be expressed as .Substitute equation(6) into equation(4), we can get the density and bulk modulus of the cloak. As mentioned above, the properties are functions of both and r. However, as shown inFigure 1(right), the cloak can be divided into N small sections, within each of which can be seen as constant, denoted as , 1,2,••• , .…”
mentioning
confidence: 99%
“…For instance, Popa et al [44] and Zigoneanu et al [41] have demonstrated the effectiveness of ground cloaks experimentally in the two-and three-dimensional cases, respectively. An acoustic cloak comprised perforated plates for generating virtual images was validated by Hu et al [45]. Apart from the above-mentioned homogeneous cloaks, an annulus cloak constructed with a network of acoustic circuit elements [46], and a directional threedimensional cloak designed on the basis of the scattering cancellation technique [47] were also validated experimentally.…”
Section: Introductionmentioning
confidence: 99%